Unidad de producción como apoyo pedagógico para desarrollar destrezas en soldadura en los estudiantes de bachillerato técnico de la unidad educativa la Alborada del cantón Milagro - Jijón Fiallos, Gilberto Leonel (2017)
One of the furniture that has greater demand in the market are those used in educational institutions, which must have certain ergonomic characteristics, materials and designs that allow to prolong their useful life. The Alborada Educational Unit made its entry into the market by making school furniture that, in addition to complying with the required technical specifications, was given an added value using electrostatic impact welding that improves product quality and has meter resistance to the handling of the same. The factors of success are not so flattering because most of the processes are carried out by hand and the cost of production is higher than the market; However, the quality of the material is the strength of the product, so as they know it, they will choose it in their preferences. For each undertaking a base capital is necessary, which moves the first steps of production of the existing raw material and the machinery that is available at the moment. In conclusion, they produce a good quality product with added value that makes the difference with similar products that can compete in the market with better structural and design guarantees